A method for preparing lithium manganese iron phosphate
Patent Information
- Application Number
- CN202611144180.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
然而,导电性差、压实密度低和锰溶出等问题限制了磷酸锰铁锂的应用
[0043]第三方面,本发明提供一种磷酸锰铁锂在锂电池中的应用,所述磷酸锰铁锂为第二方面所述磷酸锰铁锂或由第一方面所述方法制备得到。
Smart Images

Figure CN123002802A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage material preparation technology, and in particular to a method for preparing lithium manganese iron phosphate. Background Technology
[0002] Lithium manganese iron phosphate (LMFP) has become a research hotspot for next-generation lithium battery cathode materials due to its advantages of high voltage and low cost. However, problems such as poor conductivity, low compaction density, and manganese leaching limit the application of LFP.
[0003] The addition of manganese can lead to excessively small and uniformly sized grinding particles, resulting in low compaction density. When different sizes of lithium manganese iron phosphate (LMFP) particles are graded, the large LMFP particles have insufficient electronic conductivity and limited lithium-ion diffusion kinetics, making it difficult to achieve optimal electrical performance. This results in a failure to balance compaction density and electrical performance. Lithium-ion batteries prepared with this graded LMFP particles will experience lattice volume changes during charge and discharge. The large LMFP particles are more prone to cracking due to concentrated mechanical stress, leading to the shedding of the LMFP-containing active material layer and a decline in battery cycle performance.
[0004] Therefore, there is still an urgent need for a method to prepare lithium manganese iron phosphate that can provide a good three-dimensional conductive network structure, good porosity, improve electrolyte wetting effect to enhance lithium ion diffusion kinetics, and simultaneously take into account the material's compaction density and electrical properties. Summary of the Invention
[0005] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a method for preparing lithium manganese iron phosphate. By adding material A containing titanium hydride and carbon nanotubes to the preparation process of the lithium manganese iron phosphate precursor, the prepared lithium manganese iron phosphate precursor possesses a three-dimensional conductive network structure, ensuring the optimal electrical performance of the precursor. The precursor also features a porous structure supported by a carbon nanotube framework formed by titanium hydride, which improves the wetting effect of the electrolyte, reduces lithium ion diffusion pathways, and enhances lithium ion diffusion kinetics. The preparation method provided by this invention produces lithium manganese iron phosphate with high compaction density, retains the structural and functional characteristics of the precursor, possesses a three-dimensional conductive network structure, improves electrolyte wetting effect, reduces lithium ion diffusion pathways, enhances lithium ion diffusion kinetics, and simultaneously ensures good electrical performance.
[0006] In a first aspect, the present invention provides a method for preparing lithium manganese iron phosphate, comprising the following steps:
[0007] S1: Preparation of material A: Titanium hydride, carbon nanotubes and water are mixed, stirred and dispersed, and the water is evaporated under ultrasonic heating to obtain material A; S2: Preparation of precursor 1: Lithium source 1, iron source 1, manganese source 1, phosphorus source 1, carbon source 1 and solvent 1 are mixed, and the slurry particle size D is controlled. 50 The particle size is 0.4 μm to 0.6 μm, resulting in slurry 1; material A prepared in step S1 is added to slurry 1, mixed evenly, and after the first spray drying, the first sintering is performed to obtain precursor 1; S3: Preparation of lithium manganese iron phosphate: Lithium source 2, iron source 2, manganese source 2, phosphorus source 2, carbon source 2 and solvent 2 are mixed, and the slurry particle size D is controlled. 50 The thickness is 0.2 μm to 0.5 μm to obtain slurry 2; the precursor 1 prepared in step S2 is added to slurry 2, mixed evenly, and then spray-dried for a second time, followed by a second sintering to obtain the lithium manganese iron phosphate.
[0008] In this invention, by adding material A containing titanium hydride and carbon nanotubes to the preparation process of lithium manganese iron phosphate precursor (i.e., precursor 1), the prepared lithium manganese iron phosphate precursor has a three-dimensional conductive network structure, which ensures the electrical performance of the prepared lithium manganese iron phosphate precursor. The lithium manganese iron phosphate precursor has a porous structure with a carbon nanotube framework supported by titanium hydride, which can improve the wetting effect of the electrolyte, reduce the diffusion path of lithium ions, and improve the diffusion kinetics of lithium ions. The preparation method provided by this invention produces lithium manganese iron phosphate with high compaction density, retains the structural and functional characteristics of lithium manganese iron phosphate precursor, has a three-dimensional conductive network structure, can improve the wetting effect of the electrolyte, reduce the diffusion path of lithium ions, improve the diffusion kinetics of lithium ions, and at the same time ensure good electrical performance.
[0009] In this invention, the above preparation method may further include at least one of the following technical features: According to an embodiment of the present invention, in step S1, the mass ratio of titanium hydride to carbon nanotubes is (1~5):(1~5); specifically, the mass ratio of titanium hydride to carbon nanotubes is 1:1, 2:1, 3:1, 4:1, 5:1, 1:2, 3:2, 5:2, 1:3, 2:3, 4:3, 5:3, 1:4, 3:4, 5:4, 1:5, 2:5, 3:5, 4:5 or any ratio within the above range, preferably (1~2):1.
[0010] According to an embodiment of the present invention, in step S1, a slurry with a solid content of 5% to 60% is prepared by mixing titanium hydride, carbon nanotubes and water; specifically, a slurry with a solid content of 5%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 30%, 40%, 50%, 60% or any value within any two of the above values is prepared by mixing titanium hydride, carbon nanotubes and water.
[0011] According to an embodiment of the present invention, the temperature in the ultrasonic heating condition is 90℃-110℃; specifically, the temperature in the ultrasonic heating condition is 90℃, 95℃, 100℃, 105℃, 110℃ or any value within the range of any two of the above values.
[0012] According to an embodiment of the present invention, the ultrasonic frequency in the ultrasonic heating condition is 20kHz-30kHz; specifically, the ultrasonic frequency in the ultrasonic heating condition is 20kHz, 25kHz, 30kHz or any value within the range of any two of the above values.
[0013] In this invention, titanium hydride, an insoluble solid, is used as a pore-expanding agent. It decomposes to produce hydrogen gas at high temperatures of 400℃-800℃. Material A, containing titanium hydride and carbon nanotubes, is added to the preparation process of lithium manganese iron phosphate precursor. The generated hydrogen gas can form bubbles in the lithium manganese iron phosphate precursor (i.e., precursor 1) during preparation. After cooling, pores are left, thereby forming a three-dimensional conductive network structure. The three-dimensional conductive network structure is supported by a carbon nanotube framework. The synergistic effect of titanium hydride and carbon nanotubes can ensure the electrical performance of the prepared lithium manganese iron phosphate precursor, improve the wetting effect of the electrolyte, reduce the diffusion path of lithium ions, and improve the diffusion kinetics of lithium ions.
[0014] According to an embodiment of the present invention, the lithium source 1 and the lithium source 2 are each independently at least one of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium dihydrogen phosphate; the lithium source 1 and the lithium source 2 may be the same or different.
[0015] According to an embodiment of the present invention, the iron source 1 and the iron source 2 are each independently at least one of ferrous oxalate, ferric phosphate, ferrous acetate, ferric oxide, and ferric manganese phosphate; the iron source 1 and the iron source 2 may be the same or different.
[0016] According to an embodiment of the present invention, manganese source 1 and manganese source 2 are each independently at least one of manganese tetroxide, manganese ferric phosphate, manganese acetate, and manganese chloride; manganese source 1 and manganese source 2 may be the same or different.
[0017] According to an embodiment of the present invention, phosphorus source 1 and phosphorus source 2 are each independently at least one of phosphoric acid, lithium dihydrogen phosphate, iron phosphate, ammonium hydrogen phosphate, and iron manganese phosphate; phosphorus source 1 and phosphorus source 2 may be the same or different.
[0018] According to an embodiment of the present invention, carbon source 1 and carbon source 2 are each independently at least one of glucose, sucrose, and starch; carbon source 1 and carbon source 2 may be the same or different.
[0019] According to an embodiment of the present invention, solvent 1 and solvent 2 are each independently water.
[0020] According to an embodiment of the present invention, in step S2, the molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n Li :n Fe+Mn =(1.0~1.2):1; Specifically, the molar ratio of lithium, iron, manganese and phosphorus is 1.0:0.4:0.6:1, 1.02:0.5:0.5:1, 1.04:0.3:0.7:1, 1.05:0.38:0.62:1, 1.05:0.4:0.6:1, 1.1:0.38:0.62:1, 1.15:0.38:0.62:1, 1.2:0.38:0.62:1 or any ratio within the above range.
[0021] According to an embodiment of the present invention, in step S2, the amount of carbon source 1 added is 3% to 15% of the theoretical lithium manganese iron phosphate mass calculated based on the manganese source 1 added in step S2; specifically, the amount of carbon source 1 added is 3%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 6%, 7%, 8%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, 11%, 11.5%, 12%, 13%, 14%, 15% of the theoretical lithium manganese iron phosphate mass calculated based on the manganese source 1 added in step S2, or any value within the range of any two of the above values.
[0022] According to an embodiment of the present invention, the solid content of the slurry 1 is 10% to 50%; specifically, the solid content of the slurry 1 is 10%, 15%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 35%, 40%, 45%, 50%, or any value within the range of any two of the above values.
[0023] According to an embodiment of the present invention, in step S3, the molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n Li :n Fe+Mn=(1.0~1.2):1; Specifically, the molar ratio of lithium, iron, manganese and phosphorus is 1.0:0.4:0.6:1, 1.02:0.5:0.5:1, 1.04:0.3:0.7:1, 1.05:0.38:0.62:1, 1.05:0.4:0.6:1, 1.1:0.38:0.62:1, 1.15:0.38:0.62:1, 1.2:0.38:0.62:1 or any ratio within the above range.
[0024] According to an embodiment of the present invention, in step S3, the amount of carbon source 2 added is 3% to 15% of the theoretical mass of lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3; specifically, the amount of carbon source 2 added is 3%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 6%, 7%, 8%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, 11%, 11.5%, 12%, 13%, 14%, 15% of the theoretical mass of lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3, or any value within the range of any two of the above values.
[0025] According to an embodiment of the present invention, the solid content of the slurry 2 is 10% to 50%; specifically, the solid content of the slurry 2 is 10%, 15%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 35%, 40%, 45%, 50%, or any value within the range of any two of the above values.
[0026] According to an embodiment of the present invention, in step S2, the mass ratio of material A to the theoretical lithium manganese iron phosphate calculated based on the manganese source 1 added in step S2 is (0.2~2):100; specifically, the mass ratio of material A to the theoretical lithium manganese iron phosphate calculated based on the manganese source 1 added in step S2 is 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1.0:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100, 2.0:100 or any ratio within the above range; preferably (0.2~1):100.
[0027] According to an embodiment of the present invention, the temperature of the first sintering is 300℃~550℃; specifically, the temperature of the first sintering is 300℃, 350℃, 400℃, 450℃, 500℃, 550℃ or any value within the range of any two of the above values.
[0028] According to an embodiment of the present invention, the first sintering time is 3 h to 8 h; specifically, the first sintering time is 3 h, 4 h, 5 h, 6 h, 7 h, 8 h or any value within the range of any two of the above values.
[0029] According to an embodiment of the present invention, the first sintering is carried out in a protective atmosphere.
[0030] According to embodiments of the present invention, the protective atmosphere includes at least one of nitrogen atmosphere, helium atmosphere, neon atmosphere, and argon atmosphere.
[0031] According to an embodiment of the present invention, in step S2, lithium source 1, iron source 1, manganese source 1, phosphorus source 1, carbon source 1 and solvent 1 are mixed to control the slurry particle size D. 50 Slurry 1 is obtained by setting the value to 0.4 μm, 0.5 μm, 0.6 μm or any value within the range of any two of the above values.
[0032] According to an embodiment of the present invention, in step S3, the mass ratio of precursor 1 prepared in step S2 to (theoretical lithium manganese iron phosphate A + precursor 1 added in step S3) is (1~5):10; specifically, the mass ratio of precursor 1 prepared in step S2 to (theoretical lithium manganese iron phosphate A + precursor 1 added in step S3) is 1:10, 2:10, 3:10, 4:10, 5:10 or any ratio within the above range; wherein, the theoretical lithium manganese iron phosphate A is: the mass of theoretical lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3.
[0033] According to an embodiment of the present invention, the temperature of the second sintering is 700℃~850℃; specifically, the temperature of the second sintering is 700℃, 750℃, 800℃, 850℃ or any value within the range of any two of the above values.
[0034] According to an embodiment of the present invention, the second sintering time is 5h to 10h; specifically, the second sintering time is 5h, 6h, 7h, 8h, 9h, 10h or any value within the range of any two of the above values.
[0035] According to an embodiment of the present invention, the second sintering is carried out in a protective atmosphere; According to embodiments of the present invention, the protective atmosphere includes at least one of nitrogen atmosphere, helium atmosphere, neon atmosphere, and argon atmosphere.
[0036] According to an embodiment of the present invention, in step S3, lithium source 2, iron source 2, manganese source 2, phosphorus source 2, carbon source 2 and solvent 2 are mixed to control the slurry particle size D. 50 Slurry 2 is obtained by setting the value to 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm or any value within the range of any two of the above values.
[0037] According to an embodiment of the present invention, in step S2, the inlet temperature of the first spray drying is 180℃-220℃; specifically, the inlet temperature of the first spray drying is 180℃, 190℃, 200℃, 210℃, 220℃ or any value within the range of any two of the above values.
[0038] According to an embodiment of the present invention, the outlet temperature of the first spray drying is 100℃-120℃; specifically, the outlet temperature of the first spray drying is 100℃, 110℃, 120℃ or any value within the range of any two of the above values.
[0039] According to an embodiment of the present invention, the inlet temperature of the second spray drying is 180℃-220℃; specifically, the inlet temperature of the second spray drying is 180℃, 190℃, 200℃, 210℃, 220℃ or any value within the range of any two of the above values.
[0040] According to an embodiment of the present invention, the outlet temperature of the second spray drying is 100℃-120℃; specifically, the outlet temperature of the second spray drying is 100℃, 110℃, 120℃ or any value within the range of any two of the above values.
[0041] In this invention, the prepared lithium manganese iron phosphate has a high compaction density, retains the structural and functional characteristics of the lithium manganese iron phosphate precursor, has a three-dimensional conductive network structure, which can improve the wetting effect of the electrolyte, reduce the diffusion path of lithium ions, improve the diffusion kinetics of lithium ions, and at the same time ensure good electrical performance.
[0042] In a second aspect, the present invention provides a lithium manganese iron phosphate, wherein the lithium manganese iron phosphate is prepared by the preparation method described in the first aspect.
[0043] Thirdly, the present invention provides an application of lithium manganese iron phosphate in lithium batteries, wherein the lithium manganese iron phosphate is the lithium manganese iron phosphate described in the second aspect or is prepared by the method described in the first aspect.
[0044] In some embodiments, the lithium manganese iron phosphate is used as a positive electrode material or as a component of a positive electrode material in a lithium battery.
[0045] Compared with existing technologies, the preparation method provided by this invention adds a material A containing titanium hydride and carbon nanotubes to the preparation process of lithium manganese iron phosphate precursor, giving the prepared lithium manganese iron phosphate precursor a three-dimensional conductive network structure, which can ensure the electrical performance of the prepared lithium manganese iron phosphate precursor; the lithium manganese iron phosphate precursor has a porous structure with carbon nanotube framework supported by titanium hydride, which can improve the wetting effect of electrolyte, reduce the diffusion path of lithium ions, and improve the diffusion kinetics of lithium ions; the preparation method provided by this invention produces lithium manganese iron phosphate with high compaction density while ensuring good electrical performance. Attached Figure Description
[0046] Figure 1 Here is a SEM image of lithium manganese iron phosphate prepared in Example 1 of this invention; Figure 2 This is a SEM image of lithium manganese iron phosphate prepared in Example 2 of the present invention; Figure 3 The image shows a SEM image of lithium manganese iron phosphate prepared in Comparative Example 1 of this invention. Figure 4 This is a SEM image of lithium manganese iron phosphate prepared in Comparative Example 2 of this invention. Figure 5 This is a SEM image of lithium manganese iron phosphate prepared in Comparative Example 3 of this invention.
[0047] Terminology Definition Unless explicitly stated otherwise, all scopes referenced in this invention include end values.
[0048] The term "at least one" is used in this invention to describe the elements and components described herein. This is done merely for convenience and to provide a general meaning regarding the scope of the invention. This description should be understood to include one or at least one, and the singular includes the plural, unless clearly otherwise indicated.
[0049] The terms “comprising” or “including” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.
[0050] The term "solid content" refers to the proportion of non-volatile solids in a unit mass, and is calculated as follows: Solid content = (mass of solids after drying / total mass of sample before drying) × 100%.
[0051] The term "theoretical lithium manganese iron phosphate" refers to lithium manganese iron phosphate obtained based on manganese element, under an ideal crystal structure model, with a composition completely in stoichiometric proportions and free from any lattice defects, impurities, or macroscopic defects. Specifically, theoretical lithium manganese iron phosphate is based on LiMn... 0.6 Fe0.4 Based on PO4, for example, 0.4 mol of manganese tetroxide contains 1.2 mol of manganese, and theoretically, 1.2 mol of manganese can synthesize 2 mol of LiMn. 0.6 Fe 0.4 Based on 0.4 mol of manganese tetroxide, the theoretical mass of lithium manganese iron phosphate is calculated to be 314.42 g.
[0052] All numbers in this invention are approximate values, regardless of whether words such as "approximately" or "about" are used. The numerical values may vary by 1%, 2%, 5%, 7%, 8%, 10%, etc. Whenever a number with a value of N is disclosed, any number having a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, or N+ / -10% will be explicitly disclosed, where "+ / -" indicates addition or subtraction, and the range between N-10% and N+10% is also disclosed.
[0053] Unless otherwise stated, the following definitions as used in this invention shall apply. For the purposes of this invention, chemical elements are consistent with the CAS version of the periodic table and the 75th edition of the *Handbook of Chemistry and Physics*, 1994. Furthermore, general principles of organic chemistry can be found in *Organic Chemistry*, Thomas Sorrell, University Science Books, Sausalito: 1999, and *March's Advanced Organic Chemistry* by Michael B. Smith and Jerry March, John Wiley & Sons, New York: 2007, the entire contents of which are incorporated herein by reference.
[0054] Unless otherwise defined, all technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Although similar or equivalent methods and materials may be used in the implementation or testing of embodiments of this invention, suitable methods and materials are described below. All publications, patent applications, patents, and other references mentioned in this invention are incorporated herein by reference in their entirety, except where specific paragraphs are cited. In case of any conflict, this specification and its included definitions shall prevail. Furthermore, materials, methods, and examples are illustrative only and are not intended to be limiting. Detailed Implementation
[0055] According to embodiments provided by the present invention, a method for preparing lithium manganese iron phosphate is specifically provided, comprising the following steps: S1: Preparation of material A: Titanium hydride, carbon nanotubes and water are mixed, stirred and dispersed to prepare a slurry with a solid content of 5%~60%. The water is evaporated under ultrasonic conditions of 20kHz-30kHz and 90℃~110℃ to obtain material A; wherein the mass ratio of titanium hydride and carbon nanotubes is (1~5):(1~5). S2: Preparation of precursor 1: Lithium source 1, iron source 1, manganese source 1, phosphorus source 1, carbon source 1 and solvent 1 are mixed, and the slurry particle size D is controlled. 50 The particle size is 0.4 μm to 0.6 μm, resulting in slurry 1. Material A prepared in step S1 is added to slurry 1 and mixed evenly. After a first spray drying (the inlet temperature of the first spray drying is 180℃-220℃, and the outlet temperature of the first spray drying is 100℃-120℃), a first sintering is performed in a protective atmosphere (the first sintering temperature is 300℃ to 550℃, and the first sintering time is 3 h to 8 h), resulting in precursor 1. The molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n... Li :n Fe+Mn =(1.0~1.2):1; The amount of carbon source 1 added is 3%~15% of the theoretical lithium manganese iron phosphate mass calculated based on the manganese source 1 added in step S2; The solid content of slurry 1 is 10%~50%; The mass ratio of material A to the theoretical lithium manganese iron phosphate calculated based on the manganese source 1 added in step S2 is (0.2~2):100; S3: Preparation of lithium manganese iron phosphate: Lithium source 2, iron source 2, manganese source 2, phosphorus source 2, carbon source 2 and solvent 2 are mixed, and the slurry particle size D is controlled. 50 The particle size is 0.2 μm to 0.5 μm, resulting in slurry 2. Precursor 1 prepared in step S2 is added to slurry 2 and mixed evenly. A second spray drying process is performed (the inlet temperature of the second spray drying is 180℃-220℃, and the outlet temperature is 100℃-120℃). Then, a second sintering process is carried out in a protective atmosphere (the second sintering temperature is 700℃ to 850℃; the second sintering time is 5h to 10h) to obtain the lithium manganese iron phosphate. The molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n... Li :n Fe+Mn=(1.0~1.2):1; The amount of carbon source 2 added is 3%~15% of the theoretical lithium manganese iron phosphate mass calculated based on the manganese source 2 added in step S3; The solid content of slurry 2 is 10%~50%, and the mass ratio of precursor 1:(theoretical lithium manganese iron phosphate A + precursor 1 added in step S3) is (1~5):10, where theoretical lithium manganese iron phosphate A is the mass of theoretical lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3.
[0056] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific conditions are not specified in the examples, they are performed according to the conditions described in the instruction manual, conventional conditions, or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0057] Example 1 A method for preparing lithium manganese iron phosphate includes the following steps: S1: Preparation of material A: Mix 10 g titanium hydride, 5 g carbon nanotubes and 100 g water, stir and disperse, and evaporate the water under 25 kHz ultrasound and 100 °C heating conditions to obtain material A; S2: Preparation of Precursor 1: 1.05 mol lithium carbonate, 0.4 mol manganese tetroxide, 0.8 mol ferrous oxalate, 2 mol phosphoric acid, and 31.422 g glucose were dissolved and dispersed in 950 mL deionized water, ball-milled, and the particle size was measured every 30 min using a Malvern particle size analyzer. When the particle size D... 50 When the thickness reaches 0.5 μm, slurry 1 is obtained; 1.57 g of material A is added to slurry 1, mixed evenly, and subjected to a first spray drying (the inlet temperature of the first spray drying is 210℃, and the outlet temperature of the first spray drying is 110℃). Then, a first sintering is carried out in a nitrogen atmosphere (the temperature of the first sintering is 500℃, and the time of the first sintering is 6h) to obtain precursor 1. S3: Preparation of lithium manganese iron phosphate: 1.05 mol lithium carbonate, 0.4 mol manganese tetroxide, 0.8 mol ferrous oxalate, 2 mol phosphoric acid, and 31.422 g glucose were dissolved and dispersed in 950 mL deionized water, ball-milled, and the dispersion was measured every 30 min using a Malvern particle size analyzer. When the particle size D... 50When the thickness reaches 0.3 μm, slurry 2 is obtained; 78.5 g of precursor 1 prepared in step S2 and 235 mL of deionized water are added to slurry 2, mixed evenly, and subjected to a second spray drying (the inlet temperature of the second spray drying is 210℃, and the outlet temperature of the second spray drying is 110℃). Then, a second sintering is carried out in a nitrogen atmosphere (the temperature of the second sintering is 780℃; the time of the second sintering is 9h) to obtain the lithium manganese iron phosphate.
[0058] Example 2 The only difference between this embodiment and embodiment 1 is that in step S2, 0.628 g of material A is added to slurry 1.
[0059] Example 3 The only difference between this embodiment and embodiment 1 is that in step S2, 3.14 g of material A is added to slurry 1.
[0060] Example 4 The only difference between this embodiment and Embodiment 1 is that in step S1, the total mass of titanium hydride and carbon nanotubes remains unchanged, and the mass ratio of titanium hydride to carbon nanotubes is 1.5:1.
[0061] Example 5 The only difference between this embodiment and Embodiment 1 is that in step S1, the total mass of titanium hydride and carbon nanotubes remains unchanged, and the mass ratio of titanium hydride and carbon nanotubes is 1:1.
[0062] Example 6 The only difference between this embodiment and Embodiment 1 is that in step S3, 134.57g of precursor 1 prepared in step S2 and 400mL of deionized water are added to slurry 2.
[0063] Comparative Example 1 (same raw materials, different preparation methods) S1: Preparation of Precursor 1: 1.05 mol lithium carbonate, 0.4 mol manganese tetroxide, 0.8 mol ferrous oxalate, 2 mol phosphoric acid, 31.422 g glucose, 10 g titanium hydride, and 5 g carbon nanotubes were dissolved and dispersed in 950 mL deionized water, ball-milled, and the dispersion was measured every 30 min using a Malvern particle size analyzer. When the particle size D... 50 When the thickness reaches 0.5 μm, slurry 1 is obtained; after the first spray drying (the inlet temperature of the first spray drying is 210℃ and the outlet temperature of the first spray drying is 110℃), the first sintering is carried out in a nitrogen atmosphere (the temperature of the first sintering is 500℃ and the time of the first sintering is 6h) to obtain precursor 1. S2: Preparation of lithium manganese iron phosphate: 1.05 mol lithium carbonate, 0.4 mol manganese tetroxide, 0.8 mol ferrous oxalate, 2 mol phosphoric acid, and 31.422 g glucose were dissolved and dispersed in 950 mL deionized water, ball-milled, and the dispersion was measured every 30 min using a Malvern particle size analyzer. When the particle size D... 50 When the thickness reaches 0.3 μm, slurry 2 is obtained; 78.5 g of precursor 1 prepared in step S2 and 235 mL of deionized water are added to slurry 2, mixed evenly, and subjected to a second spray drying (the inlet temperature of the second spray drying is 210℃, and the outlet temperature of the second spray drying is 110℃). Then, a second sintering is carried out in a nitrogen atmosphere (the temperature of the second sintering is 780℃; the time of the second sintering is 9h) to obtain the lithium manganese iron phosphate.
[0064] Comparative Example 2 (using only carbon nanotubes in step S1) The only difference between this comparative example and Example 1 is: S1: Preparation of material A: 5 g of carbon nanotubes and 100 g of water were mixed, stirred and dispersed, and the water was evaporated under the conditions of 25 kHz ultrasound and 100 °C heating to obtain material A.
[0065] Comparative Example 3 (Titanium hydride was replaced with titanium dioxide) The only difference between this comparative example and Example 1 is that: Material A was prepared by mixing 10 g of titanium dioxide, 5 g of carbon nanotubes and 100 g of water, stirring and dispersing, and then evaporating the water under the conditions of 25 kHz ultrasound and 100 °C heating to obtain material A.
[0066] Comparative Example 4 (replacing titanium hydride with lithium titanate) The only difference between this comparative example and Example 1 is that: Material A was prepared by mixing 10 g of lithium titanate, 5 g of carbon nanotubes and 100 g of water, stirring and dispersing, and then evaporating the water under the conditions of 25 kHz ultrasound and 100 °C heating to obtain material A. Comparative Example 5 (Increasing the amount of material A added) The only difference between this comparative example and Example 1 is that in step S2, 15.7 g of material A is added to slurry 1.
[0067] Performance testing: (1) Button cell battery test method: Positive electrode ratio: The active material includes any one of the lithium manganese iron phosphate prepared in Examples 1 to 6 and Comparative Examples 1 to 5, polyvinylidene fluoride (PVDF), and Super P conductive carbon black, wherein the mass ratio of lithium manganese iron phosphate:PVDF:Super P is 90:5:5.
[0068] CR2025 coin-shaped batteries were assembled in an Ar atmosphere glove box, using lithium metal as the negative electrode and a 1M LiPF6 solution as the electrolyte. The electrolyte solvent was a mixture of dimethyl carbonate, ethyl methyl carbonate, and ethylene carbonate (volume ratio 1:1:1). The electrochemical performance of the material at 0.1C was tested using a Newway battery testing system at voltages ranging from 2.0 to 4.3V. The test results are shown in Table 1. (2) Compacted density test method: The compaction density of lithium manganese iron phosphate prepared in Examples 1-6 and Comparative Examples 1-5 was tested using a powder compaction density tester. The samples were held at 3T pressure for 30 seconds and then depressurized. The test results are shown in Table 1. (3) Results: Table 1: Comparison of test data from examples and comparative examples
[0069] As shown in Table 1, the compacted density of lithium manganese iron phosphate prepared in Examples 1 to 6 is 2.35 g / cm³. 3 Using the lithium manganese iron phosphate prepared in Examples 1-6 as the active ingredient, the resulting batteries achieved an initial discharge capacity of over 153 mAh / g at a 0.1C rate, and retained over 95% of their capacity after 100 cycles. Table 1 shows that the energy density of the lithium manganese iron phosphate prepared in Examples 1-6 is higher than that of the lithium manganese iron phosphate prepared in Comparative Examples 1-5, where energy density = specific capacity × compaction density.
[0070] As shown in Comparative Example 1, even with the same raw materials, different preparation methods result in different outcomes. When titanium hydride and carbon nanotubes are directly mixed with the raw materials used to prepare lithium manganese iron phosphate precursors, the resulting lithium manganese iron phosphate precursor can form a three-dimensional conductive network structure. However, the pore expander is not distributed on the inner and outer walls of the carbon nanotubes. The pore structure formed by the pore expander is prone to collapse or deformation without the support of the carbon nanotube framework, affecting the electrical performance. Although the compaction density of the prepared lithium manganese iron phosphate is close to that of the lithium manganese iron phosphate prepared in Examples 1-6, the battery prepared using the lithium manganese iron phosphate prepared in Comparative Example 1 as the active ingredient has an initial discharge specific capacity of only 141.37 mAh / g at a 0.1C rate, and the capacity retention rate after 100 cycles is only 90.53%, indicating low energy density and poor electrical performance.
[0071] As can be seen from Comparative Example 2, when only carbon nanotubes are used to prepare material A in step S1, the prepared lithium manganese iron phosphate precursor cannot form a three-dimensional conductive network structure with a porous structure. Since lithium manganese iron phosphate has no porous structure, the electrolyte cannot effectively wet the interior of lithium manganese iron phosphate, thereby reducing lithium-ion conduction. Although the compaction density of the prepared lithium manganese iron phosphate is close to that of the lithium manganese iron phosphate prepared in Examples 1-6, the battery prepared using the lithium manganese iron phosphate prepared in Comparative Example 2 as the active ingredient has an initial discharge specific capacity of 137.15 mAh / g at a rate of 0.1C, and a capacity retention rate of 68.90% after 100 cycles. The energy density is low and the electrical performance is poor.
[0072] As shown in Comparative Example 3, when titanium hydride is replaced with titanium dioxide in step S1, titanium dioxide cannot decompose to produce hydrogen gas when heated. The prepared lithium manganese iron phosphate precursor cannot form a three-dimensional conductive network structure with a porous structure. Since lithium manganese iron phosphate has no porous structure, the electrolyte cannot effectively wet the interior of lithium manganese iron phosphate, thereby reducing lithium-ion conduction. The prepared lithium manganese iron phosphate has a low compaction density. Using the lithium manganese iron phosphate prepared in Comparative Example 3 as the active ingredient, the battery prepared has an initial discharge specific capacity of 139.47 mAh / g at a 0.1C rate, and a capacity retention rate of 70.93% after 100 cycles. The energy density is low and the electrical performance is poor.
[0073] As shown in Comparative Example 4, when titanium hydride is replaced with lithium titanate in step S1, lithium titanate cannot decompose to produce hydrogen gas when heated. The prepared lithium manganese iron phosphate precursor cannot form a three-dimensional conductive network structure with a porous structure. Since lithium manganese iron phosphate has no porous structure, the electrolyte cannot effectively wet the interior of lithium manganese iron phosphate, thereby reducing lithium-ion conduction. The prepared lithium manganese iron phosphate has a low compaction density. Using the lithium manganese iron phosphate prepared in Comparative Example 4 as the active ingredient, the battery prepared has an initial discharge capacity of 136.62 mAh / g at a 0.1C rate, and a capacity retention rate of 70.26% after 100 cycles. The energy density is low and the electrical performance is poor.
[0074] As can be seen from Comparative Example 5, the excessive addition of material A in step S2 leads to a reduction in the proportion of active components in the prepared lithium manganese iron phosphate precursor, thus reducing the specific capacity of the material. At the same time, the excessive pore structure results in a low compaction density of the prepared lithium manganese iron phosphate. Using the lithium manganese iron phosphate prepared in Comparative Example 5 as the active component, the battery prepared has an initial discharge specific capacity of 150.34 mAh / g at a 0.1C rate, and a capacity retention rate of 85.9% after 100 cycles. The energy density is low and the electrical performance is poor.
[0075] Depend on Figures 1-2 It can be seen that the lithium manganese iron phosphate prepared in Example 1 has a particle size distribution and a high compaction density. Figure 3 It can be seen that the lithium manganese iron phosphate prepared in Comparative Example 1 has more small particles and a poor particle size distribution effect. Figure 4 It can be seen that the lithium manganese iron phosphate prepared in Comparative Example 2 has a large number of large particles and poor particle size distribution. Figure 5 It can be seen that the lithium manganese iron phosphate prepared in Comparative Example 3 of this invention has a large number of large particles and poor particle size distribution.
[0076] In the description of this specification, the references to terms such as "some embodiments," "other embodiments," "examples," and "examples" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0077] Although embodiments and examples of the present invention have been shown and described above, it is understood that the above embodiments and examples are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments and examples within the scope of the present invention.
Claims
1. A method for preparing lithium manganese iron phosphate, characterized in that, Includes the following steps: S1: Preparation of material A: Titanium hydride, carbon nanotubes and water are mixed, stirred and dispersed, and the water is evaporated under ultrasonic heating to obtain material A; S2: Preparation of precursor 1: Lithium source 1, iron source 1, manganese source 1, phosphorus source 1, carbon source 1 and solvent 1 are mixed, and the slurry particle size D is controlled. 50 The particle size is 0.4 μm to 0.6 μm, resulting in slurry 1; material A prepared in step S1 is added to slurry 1, mixed evenly, and after the first spray drying, the first sintering is performed to obtain precursor 1; S3: Preparation of lithium manganese iron phosphate: Lithium source 2, iron source 2, manganese source 2, phosphorus source 2, carbon source 2 and solvent 2 are mixed, and the slurry particle size D is controlled. 50 The thickness is 0.2 μm to 0.5 μm to obtain slurry 2; the precursor 1 prepared in step S2 is added to slurry 2, mixed evenly, and then spray-dried for a second time, followed by a second sintering to obtain the lithium manganese iron phosphate.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of titanium hydride to carbon nanotubes is (1~5):(1~5); preferably (1~2):
1. Optionally, a slurry with a solid content of 5% to 60% is prepared by mixing titanium hydride, carbon nanotubes and water. Optionally, the temperature of the ultrasonic heating condition is 90℃-110℃; Optionally, the ultrasonic frequency of the ultrasonic heating condition is 20kHz-30kHz.
3. The preparation method according to any one of claims 1 or 2, characterized in that, The lithium source 1 and lithium source 2 are each independently at least one of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium dihydrogen phosphate. Optionally, the iron source 1 and the iron source 2 are each independently at least one of ferrous oxalate, ferric phosphate, ferrous acetate, ferric oxide, and ferric manganese phosphate; Optionally, manganese source 1 and manganese source 2 are each independently at least one of manganese tetroxide, manganese ferric phosphate, manganese acetate, and manganese chloride; Optionally, phosphorus source 1 and phosphorus source 2 are each independently at least one of phosphoric acid, lithium dihydrogen phosphate, iron phosphate, ammonium hydrogen phosphate, and iron manganese phosphate; Optionally, carbon source 1 and carbon source 2 are each independently at least one of glucose, sucrose, and starch; Optionally, solvent 1 and solvent 2 are each independently water.
4. The preparation method according to any one of claims 1 to 3, characterized in that, In step S2, the molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n Li :n Fe+Mn =(1.0~1.2):1; Optionally, the amount of carbon source 1 added is 3% to 15% of the theoretical mass of lithium manganese iron phosphate calculated based on the manganese source 1 added in step S2; Optionally, the solid content of the slurry 1 is 10% to 50%; Optionally, in step S3, the molar ratio of lithium, iron, manganese, and phosphorus is (1.0~1.2):(0~1):(0~1):(0.9~1.04), where n Li :n Fe+Mn =(1.0~1.2):1; Optionally, the amount of carbon source 2 added is 3% to 15% of the theoretical mass of lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3; Optionally, the solid content of the slurry 2 is 10% to 50%.
5. The preparation method according to any one of claims 1 to 4, characterized in that, In step S2, the mass ratio of material A to the theoretical lithium manganese iron phosphate calculated based on the manganese source 1 added in step S2 is (0.2~2):100; preferably (0.2~1):
100. Optionally, the temperature of the first sintering is 300℃~550℃; Optionally, the first sintering time is 3 h to 8 h; Optionally, the first sintering is carried out in a protective atmosphere; Optionally, the protective atmosphere includes at least one of nitrogen, helium, neon, and argon atmospheres.
6. The preparation method according to any one of claims 1 to 5, characterized in that, In step S3, the mass ratio of precursor 1 prepared in step S2 to (theoretical lithium manganese iron phosphate A + precursor 1 added in step S3) is (1~5):10; The theoretical lithium manganese iron phosphate A is the mass of the theoretical lithium manganese iron phosphate calculated based on the manganese source 2 added in step S3.
7. The preparation method according to any one of claims 1 to 6, characterized in that, In step S3, the temperature of the second sintering is 700℃~850℃; Optionally, the second sintering time is 5h to 10h; Optionally, the second sintering is carried out in a protective atmosphere; Optionally, the protective atmosphere includes at least one of nitrogen, helium, neon, and argon atmospheres.
8. The preparation method according to any one of claims 1 to 7, characterized in that, In step S2, the inlet temperature of the first spray drying is 180℃-220℃; Optionally, the outlet temperature of the first spray drying is 100℃-120℃; Optionally, the inlet temperature of the second spray drying is 180℃-220℃; Optionally, the outlet temperature of the second spray drying is 100°C-120°C.
9. A lithium manganese iron phosphate, characterized in that, The lithium manganese iron phosphate is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of lithium manganese iron phosphate in lithium batteries, characterized in that, The lithium manganese iron phosphate is the lithium manganese iron phosphate as described in claim 9 or prepared by the method described in any one of claims 1 to 8.
